Cytoplasmic DAXX drives SQSTM1/p62 phase condensation to activate Nrf2-mediated stress response - Yang, Yi; Willis, Thea L.; Button, Robert W.; Strang, Conor J.; Fu, Yuhua; Wen, Xue; Grayson, Portia R. C.; Evans, Tracey; Sipthorpe, Rebecca J.; Roberts, Sheridan L.; Hu, Bing; Zhang, Jianke; et al. (Nature communications, 2019)
Autophagy cargo recognition and clearance are essential for intracellular protein quality control. SQSTM1/p62 sequesters intracellular aberrant proteins and mediates cargo delivery for their selective autophagic degradation. The formation of p62 non-membrane-bound liquid compartments is critical for its function as a cargo receptor. The regulation of p62 phase separation/condensation has yet been poorly characterised. Using an unbiased yeast two-hybrid screening and complementary approaches, we found that DAXX physically interacts with p62. Cytoplasmic DAXX promotes p62 puncta formation. We further elucidate that DAXX drives p62 liquid phase condensation by inducing p62 oligomerisation. This effect promotes p62 recruitment of Keap1 and subsequent Nrf2-mediated stress response. The present study suggests a mechanism of p62 phase condensation by a protein interaction, and indicates that DAXX regulates redox homoeostasis, providing a mechanistic insight into the prosurvival function of DAXX. The autophagy protein p62 undergoes liquid-liquid phase separation but how this is regulated is unclear. Here, the authors report that the histone chaperone DAXX interacts with p62 in the cytoplasm to drive its phase separation.